Food Waste Valorization - Di Bella, Giuseppa; Tropea, Alessia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Food waste is becoming an important and growing concern at both local and global levels. According to the Food and Agriculture Organization of the United Nations (FAO), one-third of all food production is wasted globally, and in particular, 1.3 billion tons of food produced for human consumption is wasted per year, representing an economic loss of EUR 800 billion. The main foods wasted are represented by vegetables, fruits, meat, and fish. Considering the high availability and the composition of food waste, there is an increasing interest in their bio-valorization. Moreover, according to the global Sustainable Development Goals (SDGs 12 and 13), an appropriate waste management represents an essential prerequisite for the sustainable development.This reprint collects interesting manuscripts regarding innovative research focused on food waste valorization through fermentation processes for obtaining value-added products such as enzymes, feed additives, biofuels, animal feeds as well as other useful chemicals or products, food-grade pigments, and single-cell protein (SCP), enhancing food security and environmentally sustainable development.